The Role of DNA Repair in Immunological Diversity: From Molecular Mechanisms to Clinical Ramifications - Gullickson, Peter; Xu, Yunwen W.; Niedernhofer, Laura J.; Thompson, Elizabeth L.; Yousefzadeh, Matthew J. (Frontiers in Immunology, 2022)
An effective humoral immune response necessitates the generation of diverse and high-affinity antibodies to neutralize pathogens and their products. To generate this assorted immune repertoire, DNA damage is introduced at specific regions of the genome. Purposeful genotoxic insults are needed for the successful completion of multiple immunological diversity processes: V(D)J recombination, class-switch recombination, and somatic hypermutation. These three processes, in concert, yield a broad but highly specific immune response. This review highlights the importance of DNA repair mechanisms involved in each of these processes and the catastrophic diseases that arise from DNA repair deficiencies impacting immune system function. These DNA repair disorders underline not only the importance of maintaining genomic integrity for preventing disease but also for robust adaptive immunity.